Enhancing junior secondary school students' mathematics learning outcomes in Akwa Ibom State through virtual laboratory-based instruction - George, Nchelem Rosemary; Udoh, Ndianaabasi Emem (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This research examined the impact of virtual laboratory-based instruction on the learning outcomes of J.S.S students in mathematics within Akwa Ibom State. The study had dual objectives, addressing two research questions and testing two null hypotheses. Utilizing purposive sampling, a sample of 92 students from the population of 1,357 in Uyo Local Government area's public junior secondary II schools was selected. The research design was quasi-experimental. For the investigation, two intact classes were utilized. Data was collected using a twenty-item multiple-choice mathematics performance test. This test underwent validation by mathematics education experts. A reliability index of 0.84 was attained through the test-retest method. The experimental group received instruction on perimeter and area calculation for shapes like rectangles, squares, triangles, and trapeziums through virtual laboratory-based methods, while the control group received instruction through traditional physical laboratory-based methods. The two groups were pretested, post-tested and post-post-tested with the instrument to obtain performance and retention scores of the students. Statistical analysis, conducted at a significance level of 0.05, involved calculating the mean, StD, and ANCOVA. The results indicated that students instructed with virtual laboratory-based methods outperformed and retained information better than those taught through traditional physical laboratory-based methods, with statistical significance. As a recommendation, it was suggested that mathematics teachers adopt virtual laboratory-based instruction when teaching plane geometry concepts